Proceedings of the Ocean Drilling Program 1990
DOI: 10.2973/odp.proc.sr.106109.145.1990
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Electrical Resistivity and Bulk Porosity of the Upper Oceanic Crust at Hole 395A

Abstract: A long-spaced, DC electrical resistivity experiment was run during Leg 109, through over 400 m of the upper oceanic crust in Hole 395A. The same experiment had been run during Leg 83 in Hole 504B, and the results from the two holes are compared. This experiment responds to in-situ crustal resistivities over vertical and radial averaging scales of about 5-50 m, and is quite sensitive to the large-scale porosity of the crust. Apparent crustal resistivities are about 30 ohm-m through most of the pillow lavas core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
2
20
1
Order By: Relevance
“…The pulse lengthens at 1650-1700 mbsf, but the amount is small and there is no corresponding change in amplitude at this depth (Figures 7 and 8 There are no peaks in the number of fractures viewed on the borehole wails [Ayadi et al, 1998]. Resistivity measured with both the deep and shallow-penetrating laterologs is a local high, so the inferred porosity is low (Figure 1 l c, d) [Becker, 1985 Table 1 a. pores and vugs remaining from previous cycles of chemical deposition. While the circulation patterns indicated by the distribution of alteration minerals suggests that in the past this might have been a highly porous zone, the pore-filling nature of the zeolites and the low porosity inferred from the resistivity logs indicates that most open space has been filled.…”
Section: Resultsmentioning
confidence: 99%
“…The pulse lengthens at 1650-1700 mbsf, but the amount is small and there is no corresponding change in amplitude at this depth (Figures 7 and 8 There are no peaks in the number of fractures viewed on the borehole wails [Ayadi et al, 1998]. Resistivity measured with both the deep and shallow-penetrating laterologs is a local high, so the inferred porosity is low (Figure 1 l c, d) [Becker, 1985 Table 1 a. pores and vugs remaining from previous cycles of chemical deposition. While the circulation patterns indicated by the distribution of alteration minerals suggests that in the past this might have been a highly porous zone, the pore-filling nature of the zeolites and the low porosity inferred from the resistivity logs indicates that most open space has been filled.…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of apparent porosity within ocean crust can be derived from resistivity measurements recorded with the longspacing resistivity device (Becker 1985) or by the dual laterolog ). The apparent porosity is a computed value which represents both electrolytic conduction processes in pores, fractures, cracks (including microcracks) and surface conduction mechanisms; the latter are particularly important when conductive alteration minerals (e.g.…”
Section: Ocean Basement Structure the Logging Perspectivementioning
confidence: 99%
“…The relationship between porosity and resistivity for ocean floor basalts has been extensively discussed by Becker (1985) and Lovell & Pezard (1990), who concluded that the use of Archie~)s formula with a = 1.0 and m = 2.0 approximates the relationship between porosity and resistivity. However, a different law with a = 10 and m close to 1.0 has been suggested for ocean floor basalts (Flovenz et al 1985;Broglia & Moos 1998), which reflects electrolytic conduction in elongated volumes filled with pore fluid (sea water).…”
Section: Ocean Basement Structure the Logging Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Similar electrical resistivity experiments have been previously performed in DSDP holes (Francis, 1982;Von Herzen et al, 1983;Becker, 1985); however, our experiment represents a novel two-vessel approach.…”
Section: Geophysical Experimentsmentioning
confidence: 59%